Optimizing Assembly Line Production through Line Balancing: A Case Study - Saptari, Adi; Leau, Jia Xin; Mohamad, Nor Akramin (Trans Tech Publications, 2015)
In Line Balancing principles, the total workload in the assembly process is divided as evenly as possible among the workstations, without violating the sequences and relations in the assembly operations. Line balancing is important in an assembly system as it balances the line and increases the efficiency, as well as the productivity of a system. A case study was conducted in the assembly line of an electrical accessories manufacturer in Malaysia. The cycle time for each station was recorded, and the standard cycle time was estimated. The productivity, as well as the efficiency of the current assembly line, were studied. In terms of the productivity, the performance of the current systems was 500 units/worker/day, while the expected productivity was 600 units/worker/day. An assembly line setting was proposed based on the Line Balancing Method; the productivity for the proposed line increased to 671 units/worker/day, or in rough additional increase around 34%.